Dietary effects on muscle fatty acid composition of finished heifers - Silva, Regiane Gregório da; Prado, Ivanor Nunes do; Matsushita, Makoto; Souza, Nilson Evelázio de (Pesquisa Agropecuaria Brasileira, 2002)
The effects of diet on Longissimus muscle fatty acid composition was determined using 24 crossbred heifers of Simmental vs. Nelore and Limousin vs. Nelore. The experimental diets were: 1) corn and yeast (CY); 2) corn, cottonseed meal + meat and bones meal (CMB); 3) cassava hull and yeast (CHY); 4) cassava hull, cottonseed meal + meat and bones meal (CHMB). Feeding CHMB diets resulted in lower lipid and higher cholesterol contents (P < 0.05) for both crosses. Most of the identified fatty acids were monounsaturated, and the highest percentage was found to oleic acid (C18:1w9), with values ranging from 32.54 to 46.42%. Among the saturated fatty acids the palmitic acid (C16:0) showed the highest percentage, with its contents ranging between 19.40 and 32.44%. The highest polyunsaturated/saturated fatty acid ratio was of 0.30, and the lowest was of 0.08. Feeding CY diets resulted in lower cholesterol and higher polyunsaturated fatty acid contents of the Longissimus muscle.